2002
DOI: 10.1021/cm020263n
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Fiber Formation and Hydrogelation of Nucleotide Bolaamphiphiles

Abstract: Nucleotide-appended bolaamphiphiles 1−7, in which two 3‘-phosphorylated thymidine moieties are connected to both ends of a long oligomethylene spacer, have been first synthesized. Their self-assembling behavior in aqueous solutions was investigated in terms of gelling ability of water molecules. The longer homologues 6 and 7 with the C18 and C20 oligomethylene spacers, respectively, proved to be capable of gelling water very effectively (>25 000 water molecules per molecule) through spontaneous formation of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
123
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 171 publications
(128 citation statements)
references
References 34 publications
3
123
0
2
Order By: Relevance
“…For a gel in a water-rich environment, which is called a hydrogel, water participates in hydrogen bonding through bridging of charged groups (30,49,50). Self-assembled hydrogels, such as the tau 2-19 peptide gel, are characterized by the property of shear thinning, as observed here, wherein the gel viscosity decreases upon application of a force, such as that imposed by pipetting, and increases once the force is removed (30).…”
Section: Water and Hydrogen Bonding In The Tau 2-19 Gel Networkmentioning
confidence: 83%
“…For a gel in a water-rich environment, which is called a hydrogel, water participates in hydrogen bonding through bridging of charged groups (30,49,50). Self-assembled hydrogels, such as the tau 2-19 peptide gel, are characterized by the property of shear thinning, as observed here, wherein the gel viscosity decreases upon application of a force, such as that imposed by pipetting, and increases once the force is removed (30).…”
Section: Water and Hydrogen Bonding In The Tau 2-19 Gel Networkmentioning
confidence: 83%
“…169 In particular, the longer homologue 25(20) can form robust hydrogels with Mill-Q water and the buffer solutions (> pH 4.01) (Figure 25). We found that the gelation of water by 25(20) can be achieved even at concentrations of 0.2 wt% (> 25000 water molecules per hydrogelator molecule).…”
Section: Nanofiber Formation From Nucleotide-appended Bolaamphiphilicmentioning
confidence: 99%
“…4 These ribbons and tubules are single crystals that represent metastable intermediates in a crystallization pathway proceeding from filaments to plate-like crystals. 4 Nucleobase -derived amphiphiles can also form helical and tubular structures, as described for phospholipid -nucleoside conjugates 5 as well as for different single-and double-chain amphiphilic nucleobase derivatives prepared either via covalent modification 6 or by electrostatic complexation. 7 The formation of these supramolecular structures is attributed to the combination of the aggregation properties of the lipid part (hydrophobic effect) with the hydrogen bonding and π-π stacking of the nucleobase moieties.…”
mentioning
confidence: 99%